Assay of Daptomycin Injection: Development and Validation of an Environment-friendly CZE Method - Christ, Ana P.; Burin, Suelen Letícia; Marcolino, Ana I. P.; Codevilla, Cristiane Franco; Rolim, Clarice Madalena Bueno; Adams, Andrea Ines Horn (Current Pharmaceutical Analysis, 2018)
Background: Daptomycin (DPT) is the first lipopeptide antibiotic available for commercialization, approved by FDA in 2003 and not included in any official compendia. Introduction: A simple capillary zone electrophoresis method (CZE) to assay DPT injection was developed according to international guidelines. Methods: The method employed a 15 mmol L-1 pH 8.0 phosphate buffer and acetonitrile (85:15) as background electrolyte, with a voltage of 27 kV, hydrodynamic injection (50 mBar/5 s), and detection at 223 nm. The separation was achieved in a fused silica capillary with 40 cm of effective length, at 22°C, and acetylsalicylic acid was used as internal standard. The specificity was evaluated through a stress test combined with the PDA detector. As a result, the method was specific, even in the presence of degradation products. Detection was assessed around 5.5 min and the method was linear in the range of 20-120 μg mL-1 (r=0.9989). Results: The results also indicated the precision (RSD values of repeatability and intermediate precision < 2%), and accuracy (mean recovery of 101.26%) of the method. By a full factorial design 23, it was observed that none of the single factors or the combination of them affected the DPT assay, confirming the method robust. Conclusion: The method proved to be suitable to determine daptomycin injection, in quality control routine assays or in stability studies, and represents an environmentally friendly method.
Keywords: Capillary zone electrophoresis